Heat transfer to liquid metals, with observations on the effect of super-imposed free convection in turbulent flow - Buhr, Heinrich Otto (Department of Chemical Engineering, 2015)
Evaluation of the different theories of heat transfer to liquid metals requires values of the ratio of eddy diffusivities of heat and momentum, which may be obtained from temperature and velocity profiles measured in the flowing liquid metal. Temperature profiles have been reported by a number of workers, but these results are in poor agreement and this investigation was undertaken to measure further profiles and thus obtain reliable eddy diffusivities. Chapter 1 introduces the background to liquid metal heat transfer theory, and Chapter 2 contains a discussion of the experimental apparatus that was constructed for the purposes of this investigation. A description of this equipment he-s been published (Ref. 64) and the material is included here with the permission of the candidate's supervisor. Chapter 3 discusses the unsuccessful attempts to measure velocity profiles, and then goes on to consider appropriate values of the eddy diffusivity of momentum, based on the universal velocity profile. The data of Nikuradse are recommended after a careful study of all the available data and the author believes that this is a conclusion which will be useful to other workers in the field, who usually make an essentially random choice of eddy diffusivities.